INSURANCE AGAINST CYBER RISKS: COMPARATIVE STUDY - Mahdy, Elsoghair Mohamed (Veredas do Direito, 2026)
The digital community faces a myriad of legal challenges, among which a particularly significant issue is the matter of insurance against the risks associated with digitization. These risks encompass cyber-security threats, the implications of digital advancement, electronic attacks, digital hacking, infringements on digital privacy, and a host of other related vulnerabilities. In recognition of the significant challenges faced by digital institutions and their stakeholders in preserving privacy policies, protecting data, and ensuring information security, cyber insurance—also referred to as insurance against digital risks or electronic insurance—has emerged as an innovative and crucial solution. This form of insurance has arisen in response to the needs of companies to safeguard their interests and mitigate the damages resulting from cyberattacks aimed at data breaches and privacy violations. Accordingly, this research endeavors to analyze the legal issues associated with the provisions of insurance against the risks of digitization, commonly referred to as electronic insurance against cybersecurity threats. This analysis is particularly conducted given the escalation of cyberattacks and the increasing demand for electronic insurance solutions. Furthermore, this study seeks to highlight the urgent need of establishing a coherent and well-structured legal framework governing contracts related to digitization risks or electronic insurance within national legislations.